2020
DOI: 10.1186/s13045-019-0829-z
|View full text |Cite
|
Sign up to set email alerts
|

Applications of patient-derived tumor xenograft models and tumor organoids

Abstract: Patient-derived tumor xenografts (PDXs), in which tumor fragments surgically dissected from cancer patients are directly transplanted into immunodeficient mice, have emerged as a useful model for translational research aimed at facilitating precision medicine. PDX susceptibility to anti-cancer drugs is closely correlated with clinical data in patients, from whom PDX models have been derived. Accumulating evidence suggests that PDX models are highly effective in predicting the efficacy of both conventional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
215
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(254 citation statements)
references
References 106 publications
(123 reference statements)
3
215
0
2
Order By: Relevance
“…The remodeled matrix enables melanoma cells to tolerate PLX4720 via stimulating integrin β1/FAK-dependent ERK/MAPK signaling [131]. More importantly, the patient-derived tumor xenografts (PDXs) model revealed that co-inhibition of BRAF and FAK abolishes ERK reactivation in tumor stroma [132].…”
Section: Serna Involves In Ecm Remodelingmentioning
confidence: 99%
“…The remodeled matrix enables melanoma cells to tolerate PLX4720 via stimulating integrin β1/FAK-dependent ERK/MAPK signaling [131]. More importantly, the patient-derived tumor xenografts (PDXs) model revealed that co-inhibition of BRAF and FAK abolishes ERK reactivation in tumor stroma [132].…”
Section: Serna Involves In Ecm Remodelingmentioning
confidence: 99%
“…In this regard, our study aimed to establish an experimental method that focused on the generation of a bioengineered stroma, capable of persisting and sustaining SCC growth. The importance of conditioning the environment for the successful growing of human carcinomas in immunodeficient mice is a very well-known phenomenon [18][19][20]. One of the early observations regarding this issue comes from studies with prostate carcinoma cells LNCaP, which under normal conditions, do not grow in vivo, unless the site of injection is preconditioned by implantation of matrigel or coinjection with human fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evidence from pre-clinical studies supporting radio-sensitizing strategies, the number of currently active clinical trials exploring the impact of novel agents in combination with IR is limited. Among the reasons that preclude successful translation is the lack of in vivo validation using patient-derived xenograft models, which are more representative of original tumor architecture than commercially available stable cell lines [ 99 ].…”
Section: Dna Repair As a Therapeutic Target To Radio-sensitize Dmgmentioning
confidence: 99%